Sistem Informasi Catatan Perkuliahan Mahasiswa pada STMIK Pelita Nusantara Medan - Taufik, Insan (MEANS (Media Informasi Analisa dan Sistem), 2019)
Notes are minutes of the results of a writing by the process of recording or writing ideas, lists, minutes or notations of a learning activity, research, meeting or other activities that are too many to remember with memory. The problem of note that happened to STMIK Pelita Nusantara students was the lack of enthusiasm to record the results of lectures, thus influencing the entire understanding of students towards the subject. The thing that affects the lack of enthusiasm of students to record the results of lectures is the lazy habit of carrying books and stationery. Then many lecturers do not instruct students to record the results of the subjects taught. However, even though students are lazy to carry stationery, students always carry a laptop or computer while the lecture is taking place and record the results of lectures on the laptop. The output of this study is a record information system in the form of a website that can influence the spirit of student records, because each lecturer can see and assess the results of student records.